A Critical Analysis of Imagery in My Heart Leaps Up: Illuminating Wordsworth's Nature Poetry in the Context of Ecocriticism - Muhammad Haroon Jakhrani; Muhammad Hassan Shaikh (LET: Linguistics, Literature and English Teaching Journal)
This paper presents a critical analysis of the imagery used in William Wordsworth's poem My Heart Leaps Up, examining its role in the context of Ecocriticism. By offering a close reading of the poem and drawing on various eco-critical perspectives, the researcher explores the relationship between the poem's imagery and concepts such as biocentrism, anthropocentrism, eco-feminism, and deep ecology. Additionally, the researcher compares My Heart Leaps Up with other nature poems by Wordsworth and other Romantic poets, which helps us to identify particular stylistic and thematic features of the poem. This study aims to demonstrate how the use of imagery in My Heart Leaps Up connects to contemporary discourses on climate change and the anthropogenic epoch. This paper highlights the significance of My Heart Leaps Up within the broader context of Wordsworth's poetry and offers new theoretical and argumentative extensions to the reading of his nature poetry. Overall, this research contributes to our understanding of how language and imagery can be used to convey the beauty and importance of the natural world and our role in it.